Morphology Of Verbs in Alasnese - Muhammad Tahir (Lembaga Riset Ilmiah, 2022)
Geographycally languges are clasified into National and Regional or Native language to study or to investigate into regional language is important. It has been widely known that Indonesian is a national language-a language of unity Bisides, there are various regional languages which are the mother tongues of their users. Recently, The indonesian goverment encourages the offorts to develovp, preserve, and maintain the regional languages all over the country. The focus of this thesis is the Alas language,on of the native languages in Indonesia spoken by approximatelly 60.000 peoples in or out part of the Southeast Aceh District. Not only do they speak communication in the area. Language has structured element, the formation and arrangement of these elements namely, affixation, are needed to give shades of meanings. To carry out this study the writer uses a method by means of interview and provide by five native informants of Alas who live in Banda Aceh. The Alas language has four clasification of spenchj sounds which consist of : singel vowels, single consonant, vowel clusters, and consonant clusters.